Strategy Analysis for Developing a Simulation Model to Increase the Value Chain of the Palm Oil Industry Supply Chain: A System Thinking Approach: A System Thinking Approach (Case Study: Riau) - Nindy Permatasari (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The Indonesian palm oil industry has grown significantly in the last forty years. Riau Province is the largest palm oil producer in Indonesia, in 2020 Riau produced 9.7 million tons of palm oil with a plantation area of ​​almost 3.4 million hectares. Indonesia has always prioritized exporting crude oil (CPO) compared to its derivatives which have a higher selling value than raw products, then Indonesia also needs to reduce the import burden of several palm oil derivative products such as biodiesel. Although Riau is the largest palm oil-producing province, this is inversely proportional to the welfare of oil palm farmers, many areas dominated by oil palm have high poverty rates. Therefore, this study aims to develop a model of the supply chain value of the palm oil industry to create scenarios in increasing supply chain value that can increase the absorption of palm oil nationally to reduce the burden of imports and increase the income and welfare of oil palm farmers. The result of this research is a model that has useful information about the factors that can be used to increase the value of the palm oil supply chain and help the government and policymakers to be able to make policies related to oil palm.